Inhaled corticosteroids and the increased risk of pneumonia. (August 2013) - Marzoratti, Lucía; Iannella, Hernán A.; Waterer, Grant W.
Recently it has been suggested that there is a causal association between the use of inhaled corticosteroids (ICSs) and the risk of developing pneumonia in patients with chronic obstructive pulmonary disease (COPD). An increased risk of pneumonia associated with ICS use has been seen in trials with different design, different study populations and with evidence of a dose–response relationship. However, as none of these clinical trials were originally designed to assess pneumonia risk, radiographic confirmation of pneumonia was not always obtained. The extent to which pneumonia events have been confounded with acute exacerbations of COPD is unclear. As increased pneumonia events were not associated with increased mortality it remains unclear what the clinical significance of these findings are. Further complicating the association between ICSs and pneumonia is that meta-analyses restricted to budesonide trials have not shown an increased risk of pneumonia, and no association has been seen in patients with asthma. A number of mechanisms by which ICSs could increase the risk of pneumonia have been proposed, principally related to their immunosuppressive effect. Well-designed clinical trials with predefined endpoints and objective pneumonia definitions are needed before the real risk of pneumonia conferred by ICSs can be established. In the meantime, it seems reasonable to reduce ICSs given to COPD patients to the lowest effective doses, reduce the risk in individual patients by ensuring appropriate vaccination and to be vigilant for the possibility of pneumonia in patients with COPD on ICSs as they largely overlap with those of an acute exacerbation.